Advances in physical organic chemistry. - Richard, J. P. (John P.) (Academic, 2007)
Advances in Physical Organic Chemistry provides the chemical community with authoritative and critical assessments of the many aspects of physical organic chemistry. The field is a rapidly developing one, with results and methodologies finding application from biology to solid state physics. * Reviews the application of quantitative and mathematical methods towards understanding chemical problems * Multidisciplinary volumes cover organic, organometallic, bioorganic, enzymes and materials topics.